Innovation in conducting writing retreats for academic staff in higher education - Dube, B.; Maphosa, S.B.; Mershon, C.; Miner-Romanoff, K. (South African Journal of Higher Education, 2017)
How do researchers and administrators in higher education plan and carry out writing retreats for academic staff? This paper presents a distinctive approach to developing creative writing retreats for academic staff in higher education. We distill lessons from our June 2016 writing retreat, which drew participants from the University of Venda and the University of Limpopo. Responding to the South African Journal of Higher Education’s invitation to “re-imagine” writing retreats, we specify the shortcomings of linear writing retreats and discuss how to enhance collaboration, participation, and leadership capacity in planning and carrying out writing retreats. We also focus on an oft-neglected yet crucial feature of retreats, follow-up. As we show, our approach offers general insights for creative designing and implementing writing retreats.